Aktivitas Fundamental Matematis pada Kerajinan Wayang Kulit dan Aplikasinya dalam Pembelajaran Matematika - Dwi Nur Fitriyani; Ahmad Anis Abdullah (Institut Agama Islam Negeri Curup, 2022)
Mathematics is considered a difficult and boring subject because it involves numbers, symbols, and formulas. The use of culture associated with mathematics will provide new experiences for students in learning mathematics so that it will not cause boredom. The fundamental mathematical aspect that will be observed is the motif and the process by which puppets are made. The purpose of this research to describe fundamental mathematical activity according to Bishop on the shadow puppets craft. The type of research was descriptive qualitative with ethnographic approach. The data collection method that used were interviews, observations, documentation, and references. This research show that mathematics aspect of the shadow puppet craft according to Bishop: (1) counting include a long time of manufacture, number of puppets, number of tools and materials; (2) locating included the division of land, boundaries, placement of motifs; (3) measuring included fat content, calculation size and weight of the device, symmetrical motif size, color mix ratio, gradation level; (4) designing incuded the shapes of tools and materials, sketching, motifs, lines; (5) playing induded the steps and process production; and (6) explaining included the meaning of motifs, the use of tatah, and the application of color. In addition, the fundamental aspects of mathematics in the process of making puppets can be implemented in junior high schools in the form of questions.